The halo mass function and inner structure of ETHOS haloes at high redshift. Issue 1 (22nd June 2021) - Bohr, Sebastian; Zavala, Jesús; Cyr-Racine, Francis-Yan; Vogelsberger, Mark
ABSTRACT: We study the halo mass function and inner halo structure at high redshifts ( z ≥ 5) for a suite of simulations within the structure formation ETHOS framework. Scenarios such as cold dark matter (CDM), thermal warm dark matter (WDM), and dark acoustic oscillations (DAOs) of various strengths are contained in ETHOS with just two parameters h peak and k peak, the amplitude and scale of the first DAO peak. The extended Press–Schechter (EPS) formalism with a smooth- k filter is able to predict the cut-off in the halo mass function created by the suppression of small-scale power in ETHOS models (controlled by k peak ), as well as the slope at small masses that is dependent on h peak . Interestingly, we find that DAOs introduce a localized feature in the mass distribution of haloes, resulting in a mass function that is distinct in shape compared to either CDM or WDM. We find that the halo density profiles of all ETHOS models are well described by the NFW profile, with a concentration that is lower than in the CDM case in a way that is regulated by k peak . We show that the concentration–mass relation for DAO models can be well approximated by the mass assembly model based on the EPS theory, which has been proposed for CDM and WDM elsewhere. Our results can be used to perform inexpensive calculations of the halo mass function and concentration–mass relation within the ETHOS parametrization without the need of N -body simulations.